Global, regional and national burdens of bipolar disorders in adolescents and young adults: a trend analysis from 1990 to 2019 - Yifan Chen; Long Sun; Meiqi Wang; Yunxi Zhong; Xiaoying Su; Qixiu Li; Ziming Shao (General Psychiatry)
Background Bipolar disorder is identified as a cause of severe damage to the physical, psychological and social functioning of adolescents and young adults.Aims The aim of this study is to ascertain the trends in the burden of bipolar disorder among individuals aged 10–24 years at global, regional and national levels from 1990 to 2019.Methods The data analysed in this study were from the Global Burden of Diseases 2019. The numbers, rates per 100 000 population, average annual percentage changes (AAPCs) of incidence, prevalence and years lived with disability (YLDs) of bipolar disorder are reported at the global, regional and national levels among individuals aged 10–24 years. Global trends by age, sex and Social Development Index (SDI) were further analysed.Results Globally, the incidence of bipolar disorder among adolescents and young adults increased from 79.21 per 100 000 population (95% uncertainty interval (UI): 58.13 to 105.15) in 1990 to 84.97 per 100 000 population (95% UI: 61.73 to 113.46) in 2019, AAPC 0.24 (95% confidence interval (CI): 0.22 to 0.26). In the past three decades, there has been an increase in incidence, prevalence and YLDs in both males and females. The largest increase in incidence between 1990 and 2019 was observed in those aged 20–24 years old (from 51.76 per 100 000 population (95% UI: 26.81 to 87.20) in 1990 to 58.37 per 100 000 population (95% UI: 30.39 to 98.55) in 2019; AAPC 0.42 (95% CI: 0.38 to 0.47)). By the SDI quintile, the largest increase in incidence was observed in the middle SDI; however, the high SDI countries had the highest incidence. Regionally, the largest increase in incidence was observed in southern Latin America. At the national level, the most pronounced increase in the incidence was in Greenland.Conclusions The global increase in incidence among adolescents and young adults between 1990 and 2019 indicates that strategies to improve their mental health still need to be emphasised.